Dynamics of cerebral lipid peroxidation processes and antioxidant defence in rats with streptozotocin-induced diabetes complicated by ischemic-reperfusion lesion of the brain - Тkachuk, O. V.; Povar, M. A. (Journal of Education, Health and Sport, 2017)
Introduction. The role of oxidative stress in the pathogenesis of ischemic-reperfusion lesions and diabetes mellitus (DM) has been evidenced, although the dynamics of its parameters in case of DM complicated by ischemic-reperfusion lesion of the brain remains uncertain. The aim of the study. The aim of these studies was to investigate condition of lipid peroxide oxidation and activity of antioxidant enzymes in the neocortex and fields of the hippocampus of male rats with induced diabetes mellitus in the dynamics of incomplete global ischemia-reperfusion of the brain. Results. In early ischemic-reperfusion period in all the examined structures of the brain without DM the signs of oxidative stress are found which is manifested by accumulation of lipid peroxidation products against the ground of a considerable decrease of superoxide dismutase (SOD) activity. In rats with DM during this period of observation in all the brain structures except CA3 field there are signs of depression of lipid peroxidation processes and activity of antioxidant enzymes. On the 12th day of ischemic-reperfusion period in rats without DM the content of lipid peroxidation secondary products in the examined brain structures increases against the ground of reduced activity of antioxidant enzymes which is indicative of increasing signs of oxidative stress in this period. In rats with DM in this term of observation the signs of hyporeactivity of the lipoperoxidation/ antioxidant defence system remain unchanged. Conclusions. Four-month diabetes mellitus depletes the processes of lipid peroxidation and activity of antioxidant enzymes in the cortex of the frontal and occipital lobes and fields of the hippocampus, and as a result, it inhibits their response to ischemia-reperfusion of the brain both in early and remote post-ischemic periods.